FSLAM: A QGIS plugin for fast regional susceptibility assessment of rainfall-induced landslides. (April 2022) - Guo, Zizheng; Torra, Ona; Hürlimann, Marcel; Abancó, Clàudia; Medina, Vicente
Abstract: Shallow slope failures triggered by rainfall commonly pose considerable risks in mountainous areas. In order to delineate areas where landslides are more prone to occur within a region, we have designed and developed a Python QGIS plugin named Fast Shallow Landslide Assessment Model (FSLAM). The plugin integrates a simplified hydrological model and a geotechnical model based on the infinite slope theory and contains two principal modules: runoff and slope stability modelling. It can output up to 15 raster maps describing the hydrological and stability conditions in a short computational time. Firstly, we explain the design of graphical user interface and the elements of the plugin. Then, the Berguedà area in NE Spain is used as case study to present the procedure of the plugin application. The results show that the accuracy of landslide susceptibility assessment performed by FSLAM-plugin is high and the computing time is only a few minutes. Highlights: A Python QGIS plugin is developed to simulate regional landslide susceptibility. We explain the design of graphical user interface and the elements of the plugin. 15 raster maps and 6 text files are outputs regarding hydrology and stability. Plugin application and test by using landslide inventory in Berguedà (NE Spain).